Bonded substrate and method for manufacturing bonded substrate

By forming a modification layer on the bonding surface side of the substrate and performing plasma treatment and annealing treatment, the problem of possible void formation on the bonding surface of the substrate is solved, and a bonding substrate with high bonding strength is achieved, and the performance stability of the components is improved.

CN119908070APending Publication Date: 2025-04-29THE JAPAN STEEL WORKS LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380067372.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-22
Filing Date
2023-09-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

When manufacturing surface acoustic wave elements or light modulation elements, gaps may form on the bonding surfaces of substrates such as quartz substrates and lithium tantalate substrates, resulting in a low bonding strength.

Method used

By forming a modified layer on the bonding surface side of the substrate, and performing bonding and annealing treatment under conditions where plasma treatment is stable, a bonding substrate with high bonding strength is formed.

Benefits of technology

The formation of voids is effectively suppressed, the bonding strength between substrates is improved, and the performance stability of the components is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119908070A_ABST
    Figure CN119908070A_ABST
Patent Text Reader

Abstract

Provided is a bonded substrate having high bonding strength, in which formation of voids is suppressed. A bonded substrate according to an aspect of the present disclosure is a bonded substrate in which a first substrate and a second substrate are bonded to each other through their bonding surfaces. The first substrate has a first modified layer on the bonding surface side, and the second substrate has a second modified layer on the bonding surface side. A manufacturing method for a bonded substrate according to an aspect of the present disclosure is a manufacturing method for a bonded substrate for bonding a first substrate and a second substrate to each other, the method including: plasma processing a surface of the first substrate to form a first modified layer on the surface of the first substrate; plasma-treating the surface of the second substrate to form a second modified layer on the surface of the second substrate; temporarily bonding the first substrate and the second substrate to each other in a state in which the first modified layer and the second modified layer face each other; and annealing the temporarily bonded substrate to bond the first substrate and the second substrate to each other.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a bonding substrate and a method for manufacturing the bonding substrate. Background Art

[0002] With the development of communication devices such as mobile phones, it is necessary to enhance the performance of surface acoustic waves (SAW) and optical modulators. For the surface acoustic wave element forming such a SAW filter, it is necessary to widen the frequency band, for example, by improving the electromechanical coupling coefficient, and it is necessary to reduce the absolute value of the temperature coefficient of frequency (TCF). Patent document 1 discloses a technology related to such a surface acoustic wave element. For example, for an optical modulation element forming an optical modulator, it is necessary to reduce power consumption and improve its modulation performance by driving it at a lower voltage. Patent document 2 and non-patent document 1 disclose technologies related to such an optical modulation element.

[0003] Reference List

[0004] Patent Literature

[0005] Patent Document 1: Japanese Unexamined Patent Application Publication JP 2021-158666

[0006] Patent document 2: Japanese Unexamined Patent Application Publication No. JP 2010-85789.

[0007] Non-patent literature

[0008] Non-patent literature 1: Cheng Wang, Mian Zhang, Xi Chen, Maxime Bertrand, Amirhassan Shams-Ansari, Sethumadhavan Chandrasekhar, Peter Winzer & Marko Loncar "Integratedlithium niobate electro-optic modulators operating at CMOS-compatible voltages", Nature, volume562, pages 101-104 (2018). Summary of the invention

[0009] For example, when manufacturing a surface acoustic wave element or an optical modulation element, a bonding substrate in which a quartz substrate and a lithium tantalate substrate are bonded to each other, a bonding substrate in which two lithium niobate substrates are bonded to each other, or a bonding substrate in which a quartz substrate and a lithium niobate substrate are bonded to each other is used. However, depending on the bonding conditions of the substrates, voids may be formed in the bonding surfaces of the substrates, and / or the bonding strength between the substrates may be low. Other problems to be solved and novel features will become apparent from the description and drawings in this specification.

[0010] Solution to the problem

[0011] A bonding substrate according to one aspect of the present disclosure is a bonding substrate in which a first substrate and a second substrate are bonded to each other through their bonding surfaces, wherein the first substrate has a first modified layer on the bonding surface side and the second substrate has a second modified layer on the bonding surface side.

[0012] According to one aspect of the present disclosure, a method for manufacturing a bonding substrate is a method for manufacturing a bonding substrate in which a first substrate and a second substrate are bonded to each other, the method comprising the following steps: plasma treating a surface of the first substrate to form a first modified layer on the surface of the first substrate; plasma treating a surface of the second substrate to form a second modified layer on the surface of the second substrate; temporarily bonding the first substrate and the second substrate to each other in a state in which the first modified layer and the second modified layer face each other; and annealing the temporarily bonded substrates to bond the first substrate and the second substrate to each other.

[0013] Beneficial Effects of the Invention

[0014] According to the present disclosure, it is possible to provide a bonding substrate that suppresses the generation of voids and has high bonding strength, and a method for manufacturing the bonding substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a cross-sectional view showing a bonding substrate according to an embodiment;

[0016] Figure 2 is a flowchart for explaining a method for manufacturing a bonding substrate according to an embodiment;

[0017] Figure 3 is a schematic diagram for explaining a method for manufacturing a bonding substrate according to an embodiment;

[0018] Figure 4 is a graph showing the relationship between changes in plasma emission and changes in the modified layer;

[0019] Figure 5 is a graph showing the relationship between the thickness of the modified layer of the quartz substrate, the thickness of the modified layer of the lithium tantalate substrate, the void-free region, the region with satisfactory bonding strength, and the region of the present disclosure;

[0020] Figure 6 is a graph showing the relationship between the thickness of the modified layer of the quartz substrate, the thickness of the modified layer of the lithium niobate substrate, the void-free region, the region with satisfactory bonding strength, the plasma stable region, and the region of the present disclosure;

[0021] Figure 7 is a diagram showing the relationship between the thickness of the modified layer of the lithium niobate substrate (lower side), the thickness of the modified layer of the lithium niobate substrate (upper side), the void-free region, the region with satisfactory bonding strength, the plasma stable region, and the region of the present disclosure;

[0022] Figure 8 is a photograph of the modified layer of the lithium niobate substrate taken by transmission electron microscopy (TEM);

[0023] Fig. 9 It is shown Figure 8 A diagram showing the brightness distribution of the TEM photograph shown; and

[0024] Fig.10 It is a graph showing the relationship between the thickness of the modified layer and the bonding strength of each sample. DETAILED DESCRIPTION

[0025] Hereinafter, embodiments will be described with reference to the accompanying drawings.

[0026] The bonding substrate according to the embodiment is a bonding substrate in which a first substrate and a second substrate are bonded to each other through their bonding surfaces. The first substrate has a first modified layer on the bonding surface side, and the second substrate has a second modified layer on the bonding surface side. In this embodiment, the first substrate may be a quartz substrate, and the second substrate may be a lithium tantalate substrate. Alternatively, in this embodiment, the first substrate may be a quartz substrate, and the second substrate may be a lithium niobate substrate. In another alternative embodiment, the first substrate may be a first lithium niobate substrate, and the second substrate may be a second lithium niobate substrate. In other words, the bonding substrate may have a structure in which two lithium niobate substrates are bonded to each other. As an example, the case where the first substrate is a quartz substrate and the second substrate is a lithium tantalate substrate will be described below.

[0027] Figure 1 is a cross-sectional view showing a bonding substrate according to an embodiment. Figure 1 As shown, the bonding substrate 1 according to the present embodiment is a bonding substrate in which a quartz substrate 10 and a lithium tantalate substrate 20 are bonded to each other via their bonding surfaces 15. Note that the quartz substrate (first substrate) 10 serves as a supporting substrate, and the lithium tantalate substrate (second substrate) 20 serves as a piezoelectric portion.

[0028] By using the quartz substrate 10 as a supporting substrate, the frequency-temperature characteristics of the surface acoustic wave element can be improved. In addition, the propagation speed of the elastic wave of lithium tantalate is fast and its electromechanical coupling coefficient is large. Therefore, by using the lithium tantalate substrate 20 as a piezoelectric part, the frequency band of the surface acoustic wave element can be widened.

[0029] The quartz substrate 10 has a modified layer 11 (first modified layer) on the bonding surface 15 side. The lithium tantalate substrate 20 has a modified layer 21 (second modified layer) on the bonding surface 15 side. This embodiment is designed so that the modified layer 21 of the lithium tantalate substrate 20 is thinner than the modified layer 11 of the quartz substrate 10.

[0030] Specifically, in this embodiment, the thickness of the modified layer 11 of the quartz substrate 10 is greater than 2.7nm and less than or equal to 3.2nm, preferably greater than 2.9nm and less than 3.1nm. In addition, the thickness of the modified layer 21 of the lithium tantalate substrate 20 is greater than 2.2nm and less than 2.7nm, preferably greater than 2.4nm and less than 2.6nm. In this embodiment, the modified layers 11 and 21 are both amorphous layers produced by modifying the surface of the substrate, and can be formed by plasma treatment, ion radiation, etc. In addition, the modified layers 11 and 21 are amorphous layers, the main component of which is the material of the underlying substrate. In other words, the modified layer 11 is an amorphous layer with the material of the quartz substrate 10 as the main component. The modified layer 21 is an amorphous layer with the material of the lithium tantalate substrate 20 as the main component.

[0031] In this embodiment, the thickness of the quartz substrate 10 is greater than or equal to 100 μm and less than or equal to 1000 μm, and the thickness of the lithium tantalate substrate is greater than or equal to 10 μm and less than or equal to 1000 μm.

[0032] Furthermore, in this embodiment, after the quartz substrate 10 and the lithium tantalate substrate 20 are bonded to each other, the surface of the lithium tantalate substrate 20 may be polished. For example, the lithium tantalate substrate 20 may be polished to a thickness of 5 μm or less.

[0033] Next, a method for manufacturing a bonded substrate according to the present embodiment will be described. Figure 2 is a flowchart for explaining the method for manufacturing a bonding substrate according to the present embodiment. Figure 3 It is a schematic diagram for explaining the method of manufacturing a bonding substrate according to the present embodiment.

[0034] When manufacturing the bonding substrate according to the present embodiment, first, Figure 2 and Figure 3As shown, a quartz substrate (first substrate) 10 is prepared (step S1). For example, the thickness of the quartz substrate 10 is greater than 100 μm and less than 1000 μm. Next, the quartz substrate 10 is cleaned (step S2). For example, the quartz substrate 10 can be cleaned by using a chemical solution such as APM (Ammonia hydrogen Peroxide Mixture) or SPM (sulfuric acid-hydrogen peroxide mixture).

[0035] Next, the quartz substrate 10 is subjected to plasma treatment (i.e., plasma treatment) (step S3). The modified layer 11 can be formed on the surface of the quartz substrate 10 by plasma treating the quartz substrate 10. The thickness of the modified layer 11 formed on the surface of the quartz substrate 10 is greater than 2.7 nm and less than or equal to 3.2 nm, and is preferably greater than 2.9 nm and less than 3.1 nm.

[0036] Furthermore, in the present embodiment, the plasma treatment is performed on the quartz substrate 10 under the condition where the plasma emission is stable (the condition where the variation of the plasma emission is small). Figure 4 is a graph showing the relationship between changes in plasma emission and changes in the modified layer. Figure 4 As shown in FIG. 1 , when the change in plasma emission is large (i.e., the change in relative emission intensity is large), the change in the modified layer also becomes large. On the other hand, when the change in plasma emission is small (i.e., the change in relative emission intensity is small), the change in the modified layer also becomes small. Figure 4 The results shown show that a stable region is found in which the variation of plasma emission and the variation of the modified layer can be suppressed to about 1 / 5.

[0037] In this embodiment, by performing plasma treatment on the quartz substrate 10 under conditions where the variation in plasma emission is small, the variation in the in-plane film thickness of the modified layer 11 formed on the surface of the quartz substrate 10 can be reduced. Note that the variation in plasma emission can be reduced by adjusting the pressure in the chamber of the plasma treatment apparatus and the output (RF output) of the plasma.

[0038] Next, a lithium tantalate substrate (LT substrate: second substrate 20) is prepared (step S4). For example, the thickness of the lithium tantalate substrate 20 is greater than 10 μm and less than 1000 μm. Next, the lithium tantalate substrate 20 is cleaned (step S5). For example, the lithium tantalate substrate 20 can be cleaned by using a chemical solution such as APM (Ammonia hydrogen Peroxide Mixture) or SPM (sulfuric acid-hydrogen peroxide mixture).

[0039] Next, the lithium tantalate substrate 20 is subjected to plasma treatment (step S6). By plasma treating the lithium tantalate substrate 20, a modified layer 21 can be formed on the surface of the lithium tantalate substrate 20. The modified layer 21 formed on the surface of the lithium tantalate substrate 20 has a thickness of 2.2 nm to 2.7 nm, preferably 2.4 nm to 2.6 nm.

[0040] Furthermore, in the present embodiment, the lithium tantalate substrate 20 is plasma treated under a condition where plasma emission is stable (a condition where variation in plasma emission is small). By plasma treating the lithium tantalate substrate 20 under a condition where variation in plasma emission is small, variation in the in-plane film thickness of the modified layer 21 formed on the surface of the lithium tantalate substrate 20 can be reduced.

[0041] Note that the order of the processes in steps S1 to S3 and the order of the processes in steps S4 to S6 may be reversed. In other words, the processes in steps S1 to S3 may be performed after the processes in steps S4 to S6 are performed. Alternatively, the processes in steps S1 to S3 and the processes in steps S4 to S6 may be performed in parallel (simultaneously) with each other.

[0042] Next, the quartz substrate 10 and the lithium tantalate substrate 20 are temporarily bonded to each other in a state where the modified layer 11 of the quartz substrate 10 and the modified layer 21 of the lithium tantalate substrate 20 face each other (step S7). For example, after adjusting the positions of the quartz substrate 10 and the lithium tantalate substrate 20 in the in-plane direction (i.e., the positions in the horizontal direction), the quartz substrate 10 and the lithium tantalate substrate 20 are temporarily bonded to each other by moving them in the vertical direction.

[0043] After that, the temporarily bonded substrates are annealed so that the quartz substrate 10 and the lithium tantalate substrate 20 are bonded to each other (step S8). By annealing them, the modified layer 11 of the quartz substrate 10 and the modified layer 21 of the lithium tantalate substrate 20 can be firmly bonded to each other, so that the quartz substrate 10 and the lithium tantalate substrate 20 can be firmly bonded to each other. For example, the annealing temperature is 50° C. or higher and 300° C. or lower. Annealing can be performed, for example, by heating the temporarily bonded substrates in an electric furnace.

[0044] This embodiment may further include a step of polishing the surface of the lithium tantalate substrate 20 after the quartz substrate 10 and the lithium tantalate substrate 20 are bonded to each other (step S9). The polishing step may be performed, for example, by using CMP (Chemical Mechanical Polishing). For example, the lithium tantalate substrate 20 is polished to a thickness of 5 μm or less.

[0045] The bonding substrate according to the present embodiment can be manufactured by using the above-described manufacturing method (substrate bonding method).

[0046] Note that in this embodiment, the thickness of the modified layer 11 of the quartz substrate 10 and the thickness of the modified layer 21 of the lithium tantalate substrate 20 can be measured by using a TEM (Transmission Electron Microscope).

[0047] For example, the optimal conditions for plasma treatment can be obtained by measuring the thickness of the modified layers 11 and 21 using TEM and changing the conditions for plasma treatment. Then, by performing plasma treatment using the obtained optimal conditions (steps S3 and S6), the modified layers 11 and 21 having a thickness within the above range can be formed.

[0048] In the case of measuring the thickness of the modified layers 11 and 21 of the bonded substrate 1 after the quartz substrate 10 and the lithium tantalate substrate 20 are bonded to each other, TEM is used. In addition, measurement on determining which substrate the modified layers 11 and 21 originate from can be performed by combining TEM observation with elemental analysis by EDS (Energy dispersive X-ray spectrometry). For example, it can be determined that a region containing Si in the modified layer is the modified layer 11 of the quartz substrate 10, and a region containing Li or Ta in the modified layer is the modified layer 21 of the lithium tantalate substrate 20. By using the above method, the thickness of each modified layer 11 and 21 of the bonded substrate 1 can be measured. Note that in this embodiment, it is considered that the relationship between the thicknesses of the modified layers 11 and 21 does not change after the quartz substrate 10 and the lithium tantalate substrate 20 are bonded to each other.

[0049] As described in the background art, when a surface acoustic wave element is manufactured, a bonding substrate in which a quartz substrate and a lithium tantalate substrate are bonded to each other is used. However, depending on the bonding conditions of these substrates, voids may be formed in the bonding surfaces of the quartz substrate and the lithium tantalate substrate, and / or the bonding strength between these substrates may be poor.

[0050] In addition, it is generally believed that when a gap is formed on the bonding surface of the bonding substrate, the bonding strength between the bonding substrates deteriorates. However, as a result of research by the inventors of the present application, it has been found that the formation of the gap and the bonding strength are in a trade-off relationship. Therefore, it is difficult to simultaneously achieve the suppression of the formation of the gap and the strong bonding strength.

[0051] Figure 5 : is a graph showing the relationship between the thickness of the modified layer of the quartz substrate, the thickness of the modified layer of the lithium tantalate substrate, the void-free region, the region with satisfactory bonding strength, and the region of the present disclosure.

[0052] The inventors of the present application have found that when the quartz substrate 10 having the modified layer 11 having a thickness of 2.4 nm or more and 3.2 nm or less and the lithium tantalate substrate 20 having the modified layer 21 having a thickness of 1.8 nm or more and 2.7 nm or less are bonded to each other, a void-free region that can suppress the formation of voids exists on the bonding surface 15 of the bonded substrate 1. Note that the void-free region includes not only a region where voids do not exist at all but also a region where some voids are formed but to an extent that does not affect the actual use of the bonded substrate.

[0053] Furthermore, the inventors of the present application have found that when the quartz substrate 10 having the modified layer 11 having a thickness of 2.8 nm or more and 3.4 nm or less and the lithium tantalate substrate 20 having the modified layer 21 having a thickness of 2.3 nm or more and 3.2 nm or less are bonded to each other, there is a region where the bonding strength of the bonded substrate 1 is satisfactory. Note that in this embodiment, the bonding strength is 0.52 (J / m 2 ) is defined as a region where the bonding strength is satisfactory.

[0054] In view of the above relationship, the inventors of the present application have found that by bonding a quartz substrate 10 having a modified layer 11 having a thickness greater than 2.7 nm and less than or equal to 3.2 nm and a lithium tantalate substrate 20 having a modified layer 21 having a thickness of 2.2 nm or more and 2.7 nm or less to each other, a bonded substrate 1 having satisfactory bonding strength can be obtained while suppressing the formation of voids ( Figure 5 The area of ​​the present disclosure shown in ). Therefore, according to the present disclosure, a bonding substrate having high bonding strength and suppressing the formation of voids and a method for manufacturing such a bonding substrate can be provided. In addition, the bonding substrates can be prevented from being separated from each other during the grinding process by increasing the bonding strength between the bonding substrates.

[0055] In addition, in this embodiment, as described above with reference to Figure 4As described above, each of the quartz substrate 10 and the lithium tantalate substrate 20 is subjected to plasma treatment under a condition where the variation of plasma emission is small (stable condition). Therefore, it is possible to reduce the variation of the in-plane film thickness of the modified layer 11 formed on the surface of the quartz substrate 10 and the variation of the in-plane film thickness of the modified layer 21 formed on the surface of the lithium tantalate substrate 20. Therefore, it is possible to improve the bonding strength between the bonded substrates while suppressing the formation of voids.

[0056] In the above embodiment, as an example, a case where a quartz substrate is used as the first substrate and a lithium tantalate substrate is used as the second substrate has been described. However, in this embodiment, a quartz substrate may be used as the first substrate, and a lithium niobate substrate (LN substrate) may be used as the second substrate.

[0057] Figure 6 : is a graph showing the relationship between the thickness of the modified layer of the quartz substrate, the thickness of the modified layer of the lithium niobate substrate, the void-free region, the region with satisfactory bonding strength, the plasma stable region, and the region of the present disclosure. Figure 6 As shown in FIG. 1 , when a quartz substrate and a lithium niobate substrate are bonded to each other, by adjusting the thickness of the modified layer (first modified layer) of the quartz substrate to be greater than 2.2 nm and less than 3.0 nm, and adjusting the thickness of the lithium niobate substrate (second modified layer) to be greater than 1.75 nm and less than 2.25 nm, a bonded substrate ( Figure 6 In addition, Figure 6 In the figure shown, the bonding strength is 0.8 (J / m 2 The area above ) is defined as the area with satisfactory bonding strength.

[0058] For example, the thickness of the quartz substrate is greater than 10 μm and less than 1000 μm, and the thickness of the lithium niobate substrate is greater than 10 μm and less than 1000 μm. In addition, even when a quartz substrate is used as the first substrate and a lithium niobate substrate is used as the second substrate, a bonded substrate in which the quartz substrate and the lithium niobate substrate are bonded to each other can be manufactured by using the above-mentioned manufacturing method (substrate bonding method). In this case, the "lithium tantalate substrate 20" in the above-mentioned manufacturing method is replaced with a lithium niobate substrate. In addition, even in this case, after the quartz substrate and the lithium niobate substrate are bonded to each other, the surface of the lithium niobate substrate can be ground. For example, the surface of the lithium niobate substrate can be ground to a thickness of less than 10 μm. By grinding the substrate to such a thickness, the optical modulation performance of the electro-optical element can be improved.

[0059] In this embodiment, the first lithium niobate substrate may be used as the first substrate, and the second lithium niobate substrate may be used as the second substrate. In other words, two lithium niobate substrates (LN substrates) may be bonded to each other.

[0060] Figure 7 : is a graph showing the relationship between the thickness of the modified layer of the first lithium niobate substrate, the thickness of the modified layer of the second lithium niobate substrate, the void-free region, the region with satisfactory bonding strength, the plasma stable region, and the region of the present disclosure. Figure 7 As shown in FIG. 1 , when two lithium niobate substrates are bonded to each other, by adjusting the thickness of each modified layer (first modified layer and second modified layer) of each lithium niobate substrate to be greater than 1.75 nm and less than 2.25 nm, a bonded substrate ( Figure 7 ). Note that in Figure 7 In the figure shown, the bonding strength is 0.8 (J / m 2 The area above ) is defined as the area with satisfactory bonding strength.

[0061] For example, the thickness of the first lithium niobate substrate (first substrate: lower substrate) is 10 μm or more and 1000 μm or less, and the thickness of the second lithium niobate substrate (second substrate: upper substrate) is 10 μm or more and 1000 μm or less. In addition, even when the first lithium niobate substrate is used as the first substrate and the second lithium niobate substrate is used as the second substrate, a bonded substrate in which the first lithium niobate substrate and the second lithium niobate substrate are bonded to each other can be manufactured by using the above-mentioned manufacturing method (substrate bonding method). In this case, the "quartz substrate 10" and the "lithium tantalate substrate 20" in the above-mentioned manufacturing method are replaced with the first lithium niobate substrate and the second lithium niobate substrate, respectively. In addition, even in this case, after the two lithium niobate substrates (LN substrates) are bonded to each other, the surface of the second lithium niobate substrate can be ground. For example, the second lithium niobate substrate is ground to a thickness of 10 μm or less. By grinding the substrate to such a thickness, the optical modulation performance of the electro-optical element can be improved.

[0062] Figure 8 This is a photograph of the modified layer of the lithium niobate substrate taken by transmission electron microscopy (TEM). Figure 8 As shown, a modified layer is formed on the surface of a lithium niobate substrate (LN substrate). Fig. 9 It is shown Figure 8 A graph showing the brightness curve of a TEM photograph is shown. Fig. 9 The graph shown shows the measurement position on the lithium niobate substrate and the brightness at the measurement position, and shows the change in brightness when the measurement position is moved from the carbon protective film side to the lithium niobate substrate side. Fig. 9 As shown, the brightness is low at the location of the carbon protective film, and then gradually increases at the location of the modified layer. In addition, the brightness becomes high at the location of the lithium niobate substrate. In this embodiment, the thickness of the modified layer can be determined by using this brightness change. Fig. 9In the example shown, the thickness of the modified layer is 2.1 nm.

[0063] Example

[0064] Next, an example will be described.

[0065] By using the above reference Figure 2 and 3 The method described above fabricates a sample according to Example 1. Specifically, first, a quartz substrate having a thickness of 400 μm is prepared. Next, the quartz substrate is cleaned by immersing the quartz substrate in an APM solution for 10 minutes.

[0066] Next, the quartz substrate was plasma treated to form a modified layer with a thickness of 3.0 nm on the surface of the quartz substrate. The plasma treatment was performed by generating capacitively coupled plasma under a reduced pressure atmosphere. Regarding the conditions of the plasma treatment, the RF output was set to 100 W, and the treatment time was adjusted so that the thickness of the modified layer became 3.0 nm.

[0067] Note that in this example, the substrate is subjected to plasma treatment under a condition where plasma emission is stable (a condition where variation in plasma emission is small). Figure 4 As shown in FIG. 1 , plasma treatment was performed under conditions where the variation of plasma emission was small (i.e., the variation of relative emission intensity was small) and the variation of modified layer was small. The conditions for stable plasma emission were examined by adjusting the pressure in the chamber of the plasma treatment device (wafer bonding device) and the output of plasma (RF output) through experimental design. Specifically, the standard deviation of emission intensity obtained when discharge was repeated 5 times for 30 seconds was defined as the variation of plasma emission. As a result, as shown in FIG. Figure 4 As shown, the variation of plasma emission is suppressed to about 1 / 5 compared with the case where the variation of plasma emission is large.

[0068] In addition, a lithium tantalate substrate (LT substrate) having a thickness of 200 μm was prepared. Next, the lithium tantalate substrate was cleaned by immersing it in an APM solution for 10 minutes. Next, the lithium tantalate substrate was plasma-treated to form a modified layer having a thickness of 2.5 nm on the surface of the lithium tantalate substrate. The plasma treatment was performed by generating capacitively coupled plasma under a reduced pressure atmosphere. Regarding the conditions for the plasma treatment, the RF output was set to 100 W, and the treatment time was adjusted so that the thickness of the modified layer became 2.5 nm.

[0069] Next, the quartz substrate and the lithium tantalate substrate are brought into contact with each other, thereby temporarily bonding them to each other in a state where the modified layers of the quartz substrate and the lithium tantalate substrate face each other. Thereafter, the temporarily bonded substrates are annealed at 150° C., thereby bonding the quartz substrate and the lithium tantalate substrate to each other, thereby forming a bonded substrate.

[0070] Samples according to Comparative Examples 1 to 3 were manufactured by using a similar method.

[0071] In the sample according to Comparative Example 1, the thickness of the modified layer of the quartz substrate was adjusted to 3.0 nm, and the thickness of the modified layer of the lithium tantalate substrate was adjusted to 2.0 nm. In the sample according to Comparative Example 2, the thickness of the modified layer of the quartz substrate was adjusted to 3.0 nm, and the thickness of the modified layer of the lithium tantalate substrate was adjusted to 3.0 nm. In the sample according to Comparative Example 3, the thickness of the modified layer of the quartz substrate was adjusted to 2.5 nm, and the thickness of the modified layer of the lithium tantalate substrate was adjusted to 1.5 nm. The thickness of each modified layer was adjusted by changing the conditions of the plasma treatment.

[0072] For each of the samples according to Example 1 and Comparative Examples 1 to 3 manufactured as described above, it was checked whether voids were formed. A differential interference optical microscope was used to check whether voids were formed.

[0073] In addition, the bonding strength of each sample according to Example 1 and Comparative Examples 1 to 3 manufactured as described above was examined. The bonding strength was measured using a blade method. The blade method used was the same as the method described in the reference (Materials Science and Engineering R25 (1999) p. 1-88).

[0074] Fig.10 Graph showing the relationship between the thickness of the modified layer and the bonding strength of each sample. Fig.10 As shown, in the sample according to Example 1, the formation of voids was suppressed and the bonding strength was equal to or higher than the reference value (0.52 (J / m 2 )). On the other hand, in each of Comparative Examples 1 and 3, although the formation of voids was suppressed, the bonding strength was lower than the reference value. In Comparative Example 2, although the bonding strength was equal to or higher than the reference value, voids were formed.

[0075] According to the above results, in the sample according to Example 1, in which the thickness of the modified layer of the quartz substrate was 3.0 nm and the thickness of the modified layer of the lithium tantalate substrate was 2.5 nm, a bonding strength equal to or higher than the reference value was achieved and the formation of voids was suppressed.

[0076] The invention made by the inventors of the present application has been specifically described above based on the embodiments. However, it is needless to say that the present invention is not limited to the above-mentioned embodiments, and various modifications can be made without departing from the scope and spirit of the present invention.

[0077] This application is based upon and claims the benefit of priority from Japanese patent application JP 2022-151855, filed on Sep. 22, 2022, the disclosure of which is incorporated herein in its entirety by reference.

[0078] Reference numerals list

[0079] 1 Bonding substrate

[0080] 10 Quartz substrate

[0081] 11 Modified layer

[0082] 15 Joint surface

[0083] 20 Lithium Tantalate Substrate

[0084] 21 Modified layer.

Claims

1. A bonding substrate in which a first substrate and a second substrate are bonded to each other via their bonding surfaces, wherein: The first substrate has a first modified layer on the bonding surface side, and the second substrate has a second modified layer on the bonding surface side.

2. The bonding substrate according to claim 1, wherein The first substrate is a quartz substrate, and the second substrate is a lithium tantalate substrate.

3. The bonding substrate according to claim 2, wherein: The thickness of the first modified layer is greater than 2.7 nm and less than or equal to 3.2 nm, and the thickness of the second modified layer is greater than or equal to 2.2 nm and less than or equal to 2.7 nm.

4. The bonding substrate according to claim 2, wherein: The thickness of the quartz substrate is greater than or equal to 100 μm and less than or equal to 1000 μm, and the thickness of the lithium tantalate substrate is greater than or equal to 10 μm and less than or equal to 1000 μm.

5. The bonding substrate according to claim 1, wherein The first substrate is a quartz substrate, and the second substrate is a lithium niobate substrate.

6. The bonding substrate according to claim 5, wherein: The thickness of the first modified layer is greater than or equal to 2.2 nm and less than or equal to 3.0 nm, and the thickness of the second modified layer is greater than or equal to 1.75 nm and less than or equal to 2.25 nm.

7. The bonding substrate according to claim 1, wherein The first substrate is a first lithium niobate substrate, and the second substrate is a second lithium niobate substrate.

8. The bonding substrate according to claim 7, wherein: The thickness of the first modified layer is greater than or equal to 1.75 nm and less than or equal to 2.25 nm, and the thickness of the second modified layer is greater than or equal to 1.75 nm and less than or equal to 2.25 nm.

9. A method for manufacturing a bonded substrate in which a first substrate and a second substrate are bonded to each other, the method comprising the following steps: plasma treating the surface of the first substrate to form a first modified layer on the surface of the first substrate; plasma treating the surface of the second substrate to form a second modified layer on the surface of the second substrate; temporarily bonding the first substrate and the second substrate to each other in a state where the first modified layer and the second modified layer face each other; as well as The temporarily bonded substrates are annealed to bond the first substrate and the second substrate to each other.

10. The method for manufacturing a bonded substrate according to claim 9, wherein: The first substrate is a quartz substrate, the second substrate is a lithium tantalate substrate, and the second modified layer is thinner than the first modified layer.

11. The method for manufacturing a bonded substrate according to claim 10, wherein: The thickness of the first modified layer is greater than 2.7 nm and less than or equal to 3.2 nm, and the thickness of the second modified layer is greater than or equal to 2.2 nm and less than or equal to 2.7 nm.

12. The method for manufacturing a bonding substrate according to claim 10, wherein: The annealing temperature is 50°C or higher and 300°C or lower.

13. The method for manufacturing a bonding substrate according to claim 10, wherein: The thickness of the quartz substrate is greater than or equal to 100 μm and less than or equal to 1000 μm, and the thickness of the lithium tantalate substrate is greater than or equal to 10 μm and less than or equal to 1000 μm.

14. The method for manufacturing a bonded substrate according to claim 10, wherein: The method further includes a step of polishing a surface of the lithium tantalate substrate on a side opposite to a side on which the second modified layer is formed, after the quartz substrate and the lithium tantalate substrate are bonded to each other.

15. The method for manufacturing a bonded substrate according to claim 14, wherein: The lithium tantalate substrate is ground to a thickness of less than 5 μm.

16. The method for manufacturing a bonded substrate according to claim 9, wherein: The first substrate is a quartz substrate, and the second substrate is a lithium niobate substrate.

17. The method for manufacturing a bonded substrate according to claim 16, wherein: The thickness of the first modified layer is greater than or equal to 2.2 nm and less than or equal to 3.0 nm, and the thickness of the second modified layer is greater than or equal to 1.75 nm and less than or equal to 2.25 nm.

18. The method for manufacturing a bonded substrate according to claim 16, wherein: The annealing temperature is 50° C. or higher and 300° C. or lower.

19. The method for manufacturing a bonded substrate according to claim 16, wherein: The thickness of the quartz substrate is greater than or equal to 100 μm and less than or equal to 1000 μm, and the thickness of the lithium niobate substrate is greater than or equal to 10 μm and less than or equal to 1000 μm.

20. The method for manufacturing a bonded substrate according to claim 16, wherein: The method further includes a step of polishing a surface of the lithium niobate substrate on a side opposite to a side on which the second modified layer is formed, after the quartz substrate and the lithium niobate substrate are bonded to each other.

21. The method for manufacturing a bonded substrate according to claim 20, wherein: The lithium niobate substrate is ground to a thickness of less than 10 μm.

22. The method for manufacturing a bonding substrate according to claim 9, wherein: The first substrate is a first lithium niobate substrate, and the second substrate is a second lithium niobate substrate.

23. The method for manufacturing a bonded substrate according to claim 22, wherein: The thickness of the first modified layer is greater than or equal to 1.75 nm and less than or equal to 2.25 nm, and the thickness of the second modified layer is greater than or equal to 1.75 nm and less than or equal to 2.25 nm.

24. The method for manufacturing a bonding substrate according to claim 22, wherein: The annealing temperature is 50° C. or higher and 300° C. or lower.

25. The method for manufacturing a bonding substrate according to claim 22, wherein: The thickness of the first substrate is greater than or equal to 100 μm and less than or equal to 1000 μm, and the thickness of the second substrate is greater than or equal to 10 μm and less than or equal to 1000 μm.

26. The method for manufacturing a bonding substrate according to claim 22, wherein: The method further includes a step of grinding a surface of the second substrate on a side opposite to a side on which the second modified layer is formed, after the first substrate and the second substrate are bonded to each other.

27. The method for manufacturing a bonded substrate according to claim 26, wherein: The second substrate is ground to a thickness of less than 10 μm.

Citation Information

Patent Citations

  • Optical waveguide element

    JP2010085789A

  • Method for producing pluripotent stem cell population

    JP2022151855A